Plasticulture changing face of Indian Agriculture - Choudhary, Gulab; Garhwal, O P; Kaswan, P K; Yadav, Seema (Indian Farming, 2022)
Despite the fact that the country sustains more than 16 percent of the world's population with only 2.4 percent land and 4 percent water resources, the country's agricultural achievements are impressive. Agriculture employs 58.2 percent of the country's population and supports nearly 65 percent of people directly or indirectly.Â As a result, the country's potential for Plasticulture application and development is enormous. Plastics as an agricultural input break the technological barrier to improving agricultural output and offer fuel for a new period of rapid expansion following the green revolution. The Government of India agreed to form a National Committee to Promote Plasticulture Development in the country in order to promote and develop the use of plastics materials in agricultural and related fields.